ANALISA ALIRAN ANGIN PADA SUDU TURBIN ANGIN SAVONIUS TIPE-U BERBASIS SOFTWARE - Delffika Canra; Meri Rahmi; Emin Haris (Jurnal Teknologi Terapan, 2018)
Generally, wind energy sources in Indonesia's coastal areas is one of the potential sources of renewable energy (renewable energy resources) which are abundant, environmentally friendly and renewable. Savonius wind turbines can produce relatively high torque even at low wind speeds. Because it is very well developed to produce electrical energy. To get a large electric power, a large turbine construction is also needed which also certainly requires a large cost. For this reason, it is necessary to develop the dimensions of this wind turbine construction which is known as aspect ratio (Ar). The Ar that has been researched is the blade section, and other values. While the arch depth or the length of the blade arc in U -type is still likely to be researched. Therefore, it is necessary to do research on the U-type blade arc to get greater power than before. In addition to the experimental method with a prototype of the U type Savonius wind turbine with a number of 2 blades, a software-based simulation method will be carried out to analyze the air flow on the wind turbine blade. Parameters varied only with the aspect ratio of the arc length and blade cross section width, other parameters follow the previous research. This analysis will be a comparative data with experimental methods. The expected simulation results obtain the best aspect ratio (Ar) blade in capturing wind energy.